2021
DOI: 10.1007/s00170-021-07612-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on material removal mechanisms in ultrasonic assisted grinding of SiC ceramics with a defined grain distribution brazed grinding wheel

Abstract: Ultrasonic assisted grinding (UAG) is one of the most suitable methods for the processing of hard and brittle materials such as silicon carbide (SiC). During UAG of SiC, the machining quality is directly determined by the material removal mechanism. However, the research on the material removal mechanism for UAG of SiC is still not sufficiently developed. To achieve better comprehension of the material removal mechanism in UAG of SiC, this study conducted both UAG and conventional grinding (CG) tests with a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The pulse waveform during the actual machining can be approximated by a triangular waveform, as shown in Figure 6. According to the momentum theorem, in one vibration cycle, the impulse size of the average cutting force on the grinding head is equal to the impulse value of the maximum impact force, and the relationship between the cutting force š¹ applied to the grinding head as a whole and the cutting force š¹ applied to a single abrasive grain on the grinding head is shown in Equation (11). During the longitudinal torsional compound ultrasonic vibration grinding process, the head and the workpiece are in an intermittent processing state, so that the force exerted by the head is actually pulsed.…”
Section: š¹ = š‘šš¹mentioning
confidence: 99%
See 1 more Smart Citation
“…The pulse waveform during the actual machining can be approximated by a triangular waveform, as shown in Figure 6. According to the momentum theorem, in one vibration cycle, the impulse size of the average cutting force on the grinding head is equal to the impulse value of the maximum impact force, and the relationship between the cutting force š¹ applied to the grinding head as a whole and the cutting force š¹ applied to a single abrasive grain on the grinding head is shown in Equation (11). During the longitudinal torsional compound ultrasonic vibration grinding process, the head and the workpiece are in an intermittent processing state, so that the force exerted by the head is actually pulsed.…”
Section: š¹ = š‘šš¹mentioning
confidence: 99%
“…Ding et al designed a wheel with fixed structure to conduct a comparative test study on ultrasonic vibration grinding of SiC ceramics and ordinary grinding, and mainly studied the removal mechanism of SiC ceramics in the grinding process. The results show that the removal pattern of SiC ceramic materials changes from plastic removal to brittle fracture removal as the cut depth increases [ 11 ]. Zhou et al carried out ultrasound-assisted scratching tests on BK7 and JGS1 glass with a diamond indenting head, and the results showed that ultrasonic vibration could significantly increase the critical cutting depth of the brittleā€“plastic transition of the glass material, so ultrasound-assisted grinding is easier to achieve plastic-domain grinding [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic processing technology has the advantages of reducing cutting forces and heat, decreasing tool wear, optimizing chip morphology, improving surface quality, reducing subsurface damage, improving machining efficiency, etc. It has been widely applied to titanium alloys [1][2][3][4], high-temperature alloys [5][6][7][8], semiconductor wafers [9][10][11][12], engineering ceramics [13][14][15], ceramic matrix * Author to whom any correspondence should be addressed. composites [16,17], and honeycomb composites [18][19][20][21] and other difficult-to-process materials.…”
Section: Introductionmentioning
confidence: 99%